Molecular Interplay Between Cancer and Neurodegeneration: Shared Pathways and Emerging Biomarkers and a Narrative Review - Rostami, Maryam; Nakhaei, Mahnaz; Rajabi, Milad; Tolibov, Dilshod; Mamatmusayeva, Nilufar; Faiziboev, Pirmamat; Gafurova, Dilbar; Qodirova, Gulirano; Abduganiyeva, Arofat; Jalilova, Aziza; Allahyartorkaman, Mohammadreza (Asian Pacific Journal of Cancer Care, 2026)
Overview: Neurodegenerative diseases (NDs), including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS), are characterized by progressive neuronal loss, protein aggregation, oxidative stress, mitochondrial dysfunction, and impaired proteostasis. In contrast, cancer arises from uncontrolled cell proliferation, invasion, and metastasis. Methods: Despite their opposing clinical outcomes, mounting evidence highlights a complex interplay between these conditions, with epidemiological studies consistently revealing an inverse relationship: patients with NDs exhibit reduced risk of many cancers, while certain malignancies, such as melanoma in PD, occur at increased frequency. Shared molecular pathways including DNA damage response, unfolded protein response, mitophagy, redox imbalance, and chronic inflammation underpin this reciprocal association, where the same regulators can promote degeneration in neurons but survival in cancer cells. Results: Proteins central to neurodegeneration, such as tau, amyloid-β (Aβ), α-synuclein, SOD1, and TDP-43, also contribute to tumor biology by modulating apoptosis, proliferation, chemoresistance, and metastasis. For instance, tau influences microtubule stability in both AD and cancers, while Aβ and APP drive invasion in gliomas and breast cancer. Similarly, α-synuclein promotes melanoma progression, SOD1 enhances oxidative stress resistance in tumors, and TDP-43 regulates oncogenic splicing events. These dual roles position ND-associated proteins as promising biomarkers and therapeutic targets across oncology and neurology. Blood-based biomarkers derived from these proteins further expand their clinical potential, offering minimally invasive tools for early cancer detection, prognosis, and therapy monitoring. Standardized detection protocols and multimodal diagnostic strategies integrating ND-related proteins could improve patient outcomes by enabling timely intervention and personalized treatment. Conclusion: The shared yet divergent molecular networks of cancer and neurodegeneration highlight opportunities to uncover novel biomarkers and design targeted therapies that exploit common mechanisms while minimizing adverse effects, thereby bridging insights across two seemingly opposing disease domains.